Management Model Oriented to Customer Satisfaction (TQM) in Gontor Islamic Boarding School (Study Case in Gontor Campus 7) - Cecep Abdurrouf Hamidi (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Education is an important foundation to build human personality andcivilization. In the era of globalization as we feel today, it is a challenge to face theworld of education. Especially to resolve mental crisis of the younger generation.To satifiste expectations of parents, educational institutions must work harder toimprove a quality of education.The improvement quality of education is'nt beseparated from the improvement of quality management. Total Quality Management(TQM) is an approach in running a business totality, organizational competitionthrough improving products, services, people, processes and the environment. toachieve customer satisfaction. Gontor is an islamic institution provides the bestservice by educational management model, that satisfaction can be seen from theincrease and intereste a parents who send their children to this islamic institution, ifother educational institutions can take something can be applied to improving thequality of management. So can improved quality and competitiveness in education market, especially to cure mental crisis of young generation.